First-Principles Calculations of Thermoelectric Properties of Fe-Based Full- Heusler Fe2CuSi - Nurlaela, Ai; Nanto, Dwi; Azhar, Anugrah; Yuniarti, Elvan; Kristiantoro, Tony; Dedi, Dedi (Makara Journal of Science, 2024)
A first-principle study using density functional theory (DFT) and Boltzmann transport was conducted to evaluate the thermoelectric (TE) properties of an Fe-based full-Heusler alloy. The compound studied is Fe2CuSi with a Cu2MnAl-type structure. The electronic properties of Fe2CuSi were obtained using DFT calculations by running the Quantum ESPRESSO (QE) package. By contrast, TE properties, including electron thermal conductivity, electric conductivity, and Seebeck coefficient, were computed using a semi-empirical Boltzmann transport model solved through the BoltzTraP software at 50–1,500 K temperature range. The spin-orbit coupling effect on these properties was also evaluated, demonstrating notable effects on the results. Multiple electronic bands crossing the Fermi level for both spin directions were confirmed by the density of state curve, indicating the metallic behavior of Fe2CuSi. The magnitude of the figure of merit was determined by the Seebeck coefficient, electric conductivity, and electron thermal conductivity. In this study, the maximum dimensionless figure of merit was 0.027, reached at 1,000 K for the spin-down channel.